한국, 중국, 일본산 시판 천연발효 쌀식초의 이화학적 품질 및 항산화 활성 비교 - 정남혁(Namhyeok Chung); 조윤희(Yunhee Jo); 까오야핑(Yaping Gao); 구송이(Song-Yi Gu); 정용진(Yong-Jin Jeong); 권중호(Joong-Ho Kwon) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
Rice vinegar (RV) is primarily made from fermented rice or rice wine in Korea, China, and Japan. Ten commercially available naturally-fermented rice vinegars produced in Korea (KRV1~4), China (CRV1~2), and Japan (JRV1~4) were comparatively investigated for their physicochemical properties and antioxidant activities. KRV showed a significantly higher total acidity range (5.07~6.27) than both CRV (4.67~4.84) and JRV (4.64~4.84). These acidity ranges corresponded with respective standards of each country: Korea (Food Code), China (GB), and Japan (JAS). Six different organic acids were detected in RVs; acetic acid and succinic acid were the most prominent. Thirty different amino acids were detected in RVs, and main identified amino acids were alanine (KRV), phenylalanine and aspartic acid (CRV), and leucine and alanine (JRV). ${γ}-Aminobutyric$ acid was detected at high concentration in KRV1. KRV1 showed maximum total phenolic content, and DPPH and ABTS radical scavenging activities of samples were also determined with significantly increasing tendency. KRV1 (produced from brown rice with aging period of >1 year) exhibited the highest free amino acid content and antioxidant activity as compared to CRV and JRV. 쌀식초(rice vinegar, RV)는 쌀, 찹쌀, 현미 등을 주원료로 발효되며, 쌀을 주식으로 하는 아시아 지역에서 조미료로 이용되어 왔다. 본 연구에서는 한국산(KRV1~4), 중국산(CRV1~2), 일본산(JRV1~4) 시판 천연발효 쌀식초 10종을 구입하여 이들의 품질을 비교하였다. 식초의 적정산도에 대한 나라별 기준은 한국(식품공전) 4~29%, 중국(GB) 3.5% 이상, 일본(JAS) 4.2% 이상으로 10종의 시료는 모두 이 기준을 만족하였고, KRV(5.07~6.27%)가 CRV(4.67~4.84%) 및 JRV(4.64~4.84%)에 비해 유의적으로 높은 값을 나타내었다. 쌀식초의 주요 유기산으로 acetic acid와 succinic acid를 포함한 6종이 분석되었고 유리아미노산으로 30종이 분석되었으며, 한국산의 경우 alanine, 중국산의 경우 phenylalanine과 aspartic acid, 일본산의 경우 leucine과 alanine이 주요 성분으로 확인되었다. 한편 생리활성물질인 ${γ}-aminobutyric$ acid는 KRV1에서 유의적으로 높게 분석되었다. 총 폴리페놀은 KRV1에서 가장 높은 함량을 나타내었고, 이 시료의 DPPH 및 ABTS 라디칼 소거 활성 또한 유의적으로 높게 확인되었다. 천연발효 쌀식초의 이화학적 품질은 원료의 종류 및 함량, 발효방법, 숙성 여부에 따라 차이를 나타내었고, 현미를 사용하여 1년 이상 정치발효 한 KRV1에서 가장 높은 아미노산 함량 및 항산화 활성이 확인되었다.